Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12913-020-5010-4
|View full text |Cite
|
Sign up to set email alerts
|

What impact do chronic disease self-management support interventions have on health inequity gaps related to socioeconomic status: a systematic review

Abstract: Background: The social gradient in chronic disease (CD) is well-documented, and the ability to effectively selfmanage is crucial to reducing morbidity and mortality from CD. This systematic review aimed to assess the moderating effect of socioeconomic status on self-management support (SMS) interventions in relation to participation, retention and post-intervention outcomes. Methods: Six databases were searched for studies of any design published until December 2018. Eligible studies reported on outcomes from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 78 publications
(150 reference statements)
1
54
0
1
Order By: Relevance
“…A number of recent studies have demonstrated that socioeconomic status (SES) is the most decisive factor affecting health [4][5][6]. A relation exists between prevalence of diabetes and relatively disadvantaged socioeconomic position in developing and developed countries [7].…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have demonstrated that socioeconomic status (SES) is the most decisive factor affecting health [4][5][6]. A relation exists between prevalence of diabetes and relatively disadvantaged socioeconomic position in developing and developed countries [7].…”
Section: Introductionmentioning
confidence: 99%
“…This means that acceptance may be a different characteristic for well-to-do versus poor respondents. As an example, Aldoory et al studied the use of text messaging to disseminate health information to rural lowincome mothers [55], and Hardman, Begg & Spelten assess the moderating effect of socioeconomic status on selfmanagement support (SMS) interventions [56].…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has called attention to the importance of evaluating Health IT interventions in ways to ensure the digital divide, is not exacerbated for low-income populations, for those with limited English pro ciency, and ethnic minority groups. In the context of expanding implementation for health IT delivered diabetes care/diabetes prevention support [27,28], it is important to understand how an expanded view of moderators of implementation delity, such as language of delivery, interact with speci ed core components, such as intervention dose, consistency or timing, when considering program sustainability, dissemination, and equity.…”
Section: Introductionmentioning
confidence: 99%